Antimicrobial Activity of Teat Antiseptic Formulations Based on Plant Extracts for Controlling Bovine Mastitis: In Vitro and In Vivo Evaluation - do Nascimento, Gabriel Michelutti [UNESP]; Rodrigues, Romário Alves [UNESP]; Brugnera, Heloisa Cristina [UNESP]; Barbosa, José Carlos [UNESP]; Favaron, Flavio Rubens; Rossi, Gabriel Augusto Marques; de Bragança, Caio Roberto Soares; Schocken-Iturrino, Ruben Pablo [UNESP]; de Ávila, Fernando Antônio [UNESP]; Cardozo, Marita Vedovelli (MDPI, 2025)
Pre- and post-milking teat antisepsis is one of the most effective methods for reducing the incidence of mastitis. Plant extracts have proven effective in reducing microorganisms, providing a natural alternative for antisepsis, along with additional benefits for teat health. This study aimed to evaluate the antimicrobial and antiseptic effects of two newly formulated products, used as pre-dipping and post-dipping agents, respectively, based on plant extracts from papain (Carica papaya), aloe vera (Aloe barbadensis), andiroba (Carapa guianensis), copaiba (Copaifera officinalis), tea tree (Melaleuca alternifolia), and barbatimão (Stryphnodendron barbatiman). Minimum inhibitory concentration tests were performed in vitro, along with microbiological analyses of different bacterial groups and in vivo compliance assessments to evaluate the antimicrobial activity of the formulations, as well as the molecular identification of Staphylococcus aureus. The results demonstrated that the products were effective in vitro against the main pathogens that cause mastitis, including Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli. In the in vivo assays, similar performance was observed between the tested products and the control products, indicating that the plant-extract-based formulations, applied as pre-dipping and post-dipping agents, effectively reduced the microbial load on the teats. The effects were equivalent to those of hydrogen-peroxide- and iodine-based products, being able to reduce the total microbial load by more than 80%.